Implementation of the Problem Based Learning Model with Realia Media to Improve Elementary School Students’ Critical Thinking Skills - Syaipia Laila Nur Fitriani; Dede Trie Kurniawan; Mega Laeni (Elementaria: Journal of Educational Research, 2026)
This research is motivated by the low critical thinking skills of fourth grade elementary school students, such as difficulty analyzing problems, expressing logical opinions, and drawing conclusions. This is caused by an inappropriate learning model so that students are less active in solving problems. Efforts made are implementing a Problem Based Learning (PBL) model assisted by realia media so that students learn through real problems and concrete objects. This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by realia media on students' critical thinking skills, the effect of the Inquiry model assisted by YouTube video media on the control class, and the differences in critical thinking skills of the two classes. The method used is a quasi-experiment with the Matching-Only Pre-test-Post-test Control Group Design, involving 24 students of Neglasari State Elementary School and 22 students of Mekarsari State Elementary School. The results show an increase in average scores in both classes, with the post-test of the experimental class (42.58) higher than the control class (27.90). The significance value of 0.000 is smaller than 0.005 so that Ha is accepted and H0 is rejected. It can be concluded that there are differences in critical thinking skills between students who use the Problem Based Learning (PBL) model and those who use the Inquiry model assisted by YouTube video media. Keywords: Critical Thinking, Problem Based Learning (PBL) Model, Realia Media, Force.